Second-Coordination Sphere Effect on the Reactivity of Vanadium–Peroxo Complexes: A Computational Study - Muhammad Qadri Effendy Mubarak; Sam P. de Visser (American Chemical Society (United States), 2024)
Inorg. Chem.2019, 58, 15741−15750